Faktor Pengungkapan ESG, Tata Kelola, Efisiensi Operasional, dan Penggunaan AI dalam Kinerja Perusahaan Teknologi - Ramdhani Ahmad Fariz Putra Setiawan; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2025)
Technology companies face the dynamic challenge of improving financial performance while meeting sustainability expectations. This research aims to analyze the contribution of ESG (Environmental, social, and governance) disclosure, corporate governance, operational efficiency, and the use of AI to the financial performance of technology companies. The research method uses a quantitative approach with multiple linear regression analysis, using secondary data from annual reports of technology companies listed on the IDX during 2018–2023. The research results show that ESG disclosure positively influences a company's reputation and access to capital. Good governance increases transparency and accountability, while operational efficiency and the application of AI have proven significant in optimizing productivity and innovation. In conclusion, these four factors support each other in creating added value and competitiveness for technology companies in the global market. These findings imply the importance of an integrated strategy in managing sustainability, operational and technological aspects to achieve sustainable financial performance.